Acceptance and Commitment Therapy for people with dementia experiencing psychological distress - Robinson, Amie (2022)
Introduction: People with dementia can experience a high level of psychological distress (Muliyala & Varghese, 2010; Badrakalimuthu & Tarbuck, 2012). Although psychological approaches have been proposed as potential treatments for this population (NICE, 2018), there is indication that older adults (Laidlaw, 2013) and people with dementia have reduced opportunities for psychological treatments designed to improve their wellbeing. An increasing number of studies have evidenced the efficacy of Acceptance and Commitment Therapy (ACT) for anxiety, depression (Ӧst, 2014), distress in older adults (Gould et al., 2021; O’Keeffe et al., 2021) and illness-related distress (Mccracken & Gutiérrez-martínez, 2011). But, to date, no studies have investigated the effectiveness of ACT specifically for a dementia population, despite a conceptual case for its suitability, which is empirically supported by its use with parallel populations (other long-term and neurological conditions). Furthermore, no dementia studies involving therapeutic intervention have used a case series approach to explicitly examine change processes, integral for understanding and refining interventions. Therefore, the current research aims to investigate the effectiveness and acceptability of ACT for people with dementia.